(untitled) (LEGAL DIALOGICA, 2025)
This study aims to determine, understand, and analyze Restorative Justice in resolving domestic violence crimes at the prosecution level based on Indonesian laws and regulations. The research method used is normative research, namely a legal research method that uses secondary legal materials or library research that focuses on examining legal norms as the main basis, including relevant regulations, books, articles, journals, research results, papers, and others relevant to the issues to be discussed. The results of this study indicate that domestic violence is one of the most frequently occurring crimes. To provide protection to victims, fast and responsive handling is needed. Since the issuance of Attorney General Regulation Number 15 of 2020 concerning the Termination of Prosecution Based on Restorative Justice, a new breakthrough has emerged in resolving criminal cases. The restorative justice approach focuses on achieving peace between the perpetrator and the victim of the crime. The main principle of this approach is a mutually beneficial solution, with the hope that the victim can forgive the perpetrator’s actions. The recommendation in this study is that regular evaluation of the implementation of Restorative Justice is needed, especially in cases of Domestic Violence, to measure its effectiveness and impact on reducing the number of cases of violence and victim recovery. Abstrak: Penelitian ini bertujuan untuk mengetahui, memahami, dan menganalisis Restorative Justice dalam penyelesaian tindak pidana kekerasan dalam rumah tangga pada tingkat penuntutan berdasarkan peraturan perundang-undangan di Indonesia. Metode penelitian yang digunakan adalah penelitian normatif, yakni suatu metode penelitian hukum yang menggunakan bahan hukum sekunder atau merupakan penelitian keputakaan yang berfokus mengkaji norma hukum sebagai dasar utama yang meliputi peraturan yang relevan, buku-buku, artikel, jurnal, hasil penelitian, makalah, dan sebagiannya yang relevan permasalahan yang akan dibahas. Hasil penelitian ini menunjukkan kekerasan dalam rumah tangga merupakan salah satu tindak pidana yang kerap terjadi. Untuk memberikan perlindungan kepada korban, dibutuhkan penanganan yang cepat dan tanggap. Sejak diterbitkannya Peraturan Jaksa Agung Nomor 15 Tahun 2020 tentang Penghentian Penuntutan Berdasarkan Keadilan Restoratif (Restorative Justice), muncul terobosan baru dalam penyelesaian perkara pidana. Pendekatan keadilan restoratif berfokus pada tercapainya perdamaian antara pelaku dan korban tindak pidana. Prinsip utama dari pendekatan ini adalah solusi yang saling menguntungkan, dengan harapan korban dapat memberikan maaf atas perbuatan pelaku. Rekomendasi dalam penelitian ini diperlukan evaluasi yang secara berkala terhadap penerapan Restorative Justice, khususnya dalam kasus Kekerasan Dalam Rumah Tangga, untuk mengukur efektivitas dan dampaknya terhadap penurunan angka kekerasan serta pemulihan korban.